2010
DOI: 10.1254/jphs.09282fp
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin- and Ca2+-Dependent Facilitation and Inactivation of the CaV1.2 Ca2+ Channels in Guinea-Pig Ventricular Myocytes

Abstract: Abstract. The L-type Ca 2+ channel (Ca V 1.2) shows clear Ca 2+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 49 publications
(45 reference statements)
9
38
0
Order By: Relevance
“…Since short preIQ and IQ peptides can bind with one molecule each of CaM, it is reasonable to state that the longer preIQ-IQ peptide binds with two molecules of CaM at the same time. This idea is consistent with our hypothesis that CaM binding to one site plays a role in CDF and the binding of the second CaM to the other site triggers CDI (24).…”
Section: Two Molecules Of Cam Bind To the C-terminus Of Cav12 Channelsupporting
confidence: 92%
“…Since short preIQ and IQ peptides can bind with one molecule each of CaM, it is reasonable to state that the longer preIQ-IQ peptide binds with two molecules of CaM at the same time. This idea is consistent with our hypothesis that CaM binding to one site plays a role in CDF and the binding of the second CaM to the other site triggers CDI (24).…”
Section: Two Molecules Of Cam Bind To the C-terminus Of Cav12 Channelsupporting
confidence: 92%
“…Single ventricular myocytes of guinea-pig heart were obtained with an enzymatic dissociation protocol. 19,20) Briefly, animals were anaesthetized intraperitoneally with 100 mg/kg sodium pentoparbital. The heart was dissected out quickly and was mounted on a Langendorff apparatus for digestion.…”
Section: Animals and Cell Preparationmentioning
confidence: 99%
“…-dependent regulations of the Cav1.2 channel [9][10][11]. Numerous studies have suggested that the tethering or binding sites in the C-terminal tail of Cav1.2 include an isoleucineglutamine motif (i.e., the IQ motif, a consensus CaM-binding motif in many proteins) [9] and a PreIQ motif [10] (referred to as peptides A and C [9]) (Fig.…”
Section: +mentioning
confidence: 99%